If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + -15)(3x + 8) = 0 Reorder the terms: (-15 + 2x)(3x + 8) = 0 Reorder the terms: (-15 + 2x)(8 + 3x) = 0 Multiply (-15 + 2x) * (8 + 3x) (-15(8 + 3x) + 2x * (8 + 3x)) = 0 ((8 * -15 + 3x * -15) + 2x * (8 + 3x)) = 0 ((-120 + -45x) + 2x * (8 + 3x)) = 0 (-120 + -45x + (8 * 2x + 3x * 2x)) = 0 (-120 + -45x + (16x + 6x2)) = 0 Combine like terms: -45x + 16x = -29x (-120 + -29x + 6x2) = 0 Solving -120 + -29x + 6x2 = 0 Solving for variable 'x'. Factor a trinomial. (-8 + -3x)(15 + -2x) = 0Subproblem 1
Set the factor '(-8 + -3x)' equal to zero and attempt to solve: Simplifying -8 + -3x = 0 Solving -8 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + -3x = 0 + 8 Combine like terms: -8 + 8 = 0 0 + -3x = 0 + 8 -3x = 0 + 8 Combine like terms: 0 + 8 = 8 -3x = 8 Divide each side by '-3'. x = -2.666666667 Simplifying x = -2.666666667Subproblem 2
Set the factor '(15 + -2x)' equal to zero and attempt to solve: Simplifying 15 + -2x = 0 Solving 15 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -2x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = 0 + -15 -2x = 0 + -15 Combine like terms: 0 + -15 = -15 -2x = -15 Divide each side by '-2'. x = 7.5 Simplifying x = 7.5Solution
x = {-2.666666667, 7.5}
| 50/(7x-30) | | 4.9t^2-22t+5=0 | | 62+(6y)+[6(y+1)]=180 | | 3z+7z+9z-6= | | 2(3x+6)=12 | | 4.9t^2-23t+11=0 | | (3x-4)(x+2)=2 | | ln(56)=ln(x^2-x) | | 9x+7-10x=8x-9x-4 | | g+g+1+g+2=60 | | -9(v+7)=-4v-48 | | 49+2x=-77+11x | | 3(2x)= | | -31=3w+9-8w | | g+g+1=131 | | cb-a=9 | | 62+[4(x+2)]+(5x-7)=180 | | 9x^4-72x^2+6x+144=0 | | n/4.5=0.2/1.5 | | D-3d=70 | | 4(h+2)=8h | | 5x-4=20-x | | 52=-2x-2(2x-2) | | 0.8x+0.9(850-x)=715 | | 42=3x+6(-2x-8) | | (s^2+3s-4)+(5s-2)= | | 6d*d-5d-6=0 | | y=7-1/-7/2-9/2 | | 10+2x=0+-4x | | 96=l(l-4) | | -129=-5x-2(7x+17) | | x^2-2a-99=0 |